2019
DOI: 10.2478/phr-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Treatment is Associated with Lipid Inflammatory Response Assessed Uding Serum Platelet Activating Factor

Abstract: Hyperbaric oxygen (HBO) treatment is generally a relatively safe therapy for various conditions. However, there are some adverse side effects. For example HBO tratment has been reported to increase the production of free oxygen radicals(FRs). Furthermore, to our knowledge, no previous clinical research has been carried out to study the involvement of platelet-activating factor(PAF)as the lipid oxidative stressor in patients undergoing HBO treatment. A total of 45 patients included in this study were first give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…For example, in one study, changed levels of platelet activating factor was demonstrated in diseases after HBOT. As a result, it has been reported that the platelet activating factor increases after HBOT [8]. A recent study also reported a well increase in HBOT and HDL-associated ApoA-1 levels [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one study, changed levels of platelet activating factor was demonstrated in diseases after HBOT. As a result, it has been reported that the platelet activating factor increases after HBOT [8]. A recent study also reported a well increase in HBOT and HDL-associated ApoA-1 levels [1].…”
Section: Discussionmentioning
confidence: 99%
“…It also revealed that antiapoptotic and anti-atherosclerotic effects increased mitochondrial metabolism. It is known that elevation in free radical formation or intensive antioxidant molecule consumption after HBOT leads to post-translational modification of biological macromolecules such as lipids, lipoproteins, and enzymes [8].…”
Section: Introductionmentioning
confidence: 99%